Evaluation of contact activities of leaf extracts from four plant species against Sitophilus zeamais Motschulsky (Coleoptera: Curculiondae) - Oke, O.A.; Oyebode, G.; Onifade, E.O. (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2014)
Experiments were conducted in the Biotechnology Central Laboratory, the Biological Sciences Laboratory and the Animal House of the Department of Biological Sciences, Federal University of Agriculture, Abeokuta, Ogun State, Nigeria, to test the insecticidal effects of ethanolic and aqueous leaf extracts of Azadirachta indica, Chromolaena odorata, Mallotus oppositifolius and Tithonia diversifolia. Doses of 0.5ml, 1.0ml, 1.5ml, and 2.0ml of ethanolic leaf extracts and dose of about 0.5ml, 1.0ml and 3.0ml of aqueous extracts were applied to 20g of maize grains in which 5-13 adult Sitophilus zeamais were released for adult mortality tests. The results showed that the highest (100.00%) mortality of Sitophilus zeamais was obtained when a dose of 1.5ml of Tithonia diversifolia and 2.0ml of Chromolaena odorata, Mallotus oppositifolius and Tithonia diversifolia was applied and the least (21.21%) mortality was recorded from treatments of 0.5ml of Azadirachta indica, while for aqueous extracts the highest mortality recorded was (21.66%)and the least (0.00%) mortality of adult Sitophilus zeamais. The adult mortality of Sitophilus zeamais was non-significantly (P>0.05) different between the ethanolic extracts used and aqueous extracts used. The findings of this study also showed that ethanolic extracts were more effective than aqueous extracts used and higher dose of ethanolic leaf extracts of Chromolaena odorata, Mallotus oppositifolius and Tithonia diversifolia were more effective in protecting maize grains against Sitophilus zeamais infestation. It was observed that stains were left on the grains applied with ethanol extracts. Therefore, more research work is recommended on providing a solution that ensures the removal of the stains left by the extract on the grain.